2012
DOI: 10.1063/1.4758320
|View full text |Cite
|
Sign up to set email alerts
|

Multi-chain slip-spring model for entangled polymer dynamics

Abstract: It has been established that entangled polymer dynamics can be reasonably described by single chain models such as tube and slip-link models. Although the entanglement effect is a result of hard-core interaction between chains, linkage between the single chain models and the real multi-chain system has not been established yet. In this study, we propose a multi-chain slip-spring model where bead-spring chains are dispersed in space and connected by slip-springs inspired by the single chain slip-spring model [A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 120 publications
(168 citation statements)
references
References 68 publications
(117 reference statements)
9
159
0
Order By: Relevance
“…The longest relaxation time was found to scale with the number of entanglements, Z, as Z 3.5±0.1 , while the self-diffusion coefficient was found to scale as D cm ∼ Z −2.4±0.2 ; both agree well with experimental results [144]. Later on, the PCN model was extended to study the relationship between entanglement length and plateau modulus [145][146][147][148][149]. It was also extended to study star and branched polymers [150], nonlinear rheology [151][152][153], phase separation in polymer blends [154,155], block copolymers [156] and the dynamics of confined polymers [157].…”
Section: Slip-link Modelsupporting
confidence: 65%
“…The longest relaxation time was found to scale with the number of entanglements, Z, as Z 3.5±0.1 , while the self-diffusion coefficient was found to scale as D cm ∼ Z −2.4±0.2 ; both agree well with experimental results [144]. Later on, the PCN model was extended to study the relationship between entanglement length and plateau modulus [145][146][147][148][149]. It was also extended to study star and branched polymers [150], nonlinear rheology [151][152][153], phase separation in polymer blends [154,155], block copolymers [156] and the dynamics of confined polymers [157].…”
Section: Slip-link Modelsupporting
confidence: 65%
“…Our previous study estimates a gain in CPU time by two orders of magnitude compared to standard molecular dynamics with hard-core bead-bead interactions. 17 We also want to draw the reader's attention to the work of Chappa et al, 22 Uneyama and Masubuchi 23 as well as Ramírez-Hernández et al 24 who pursued similar approaches using multi-chain slip-spring models. In particular, Ramírez-Hernández et al 24 demonstrated good agreement of the loss and storage moduli for mono-and bidisperse polystyrene melts with experimental values.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently there have appeared newer multi-chain simulations [105,106] that fix many of the thermodynamic issues [107] associated with dynamics in the code by Masubuchi et al Therefore, these are a considerable improvement over the earlier PCN simulations. Both groups use the idea of Schieber [103] to treat the number of entanglements as a stochastic variable, which is controlled by a chemical potential bath as in a grand-canonical ensemble.…”
Section: Pcn Simulationmentioning
confidence: 99%
“…Third, if these springs do not contribute to the stress, then one expects violation of the principle of virtual work. Chappa et al [105] do not specify their stress tensor expression, whereas Uneyama and Masubuchi [106] consider both forms of stress, with and without the virtual springs.…”
Section: Pcn Simulationmentioning
confidence: 99%